Soybean for Human Consumption and Animal Feed 2020
DOI: 10.5772/intechopen.92695
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impacts of Soy Protein on Fish Gut Health

Abstract: Soy protein is the major source of protein as fishmeal replacement in fish feed because of its worldwide availability and low price. However, the presence of high carbohydrate content along with saponins, lectins, and phytates can have a negative impact on fish gut health. Based on the literature and our lab studies, dietary soybean meal can cause a dose-dependent type of distal intestine inflammation called enteritis in commercial fish species including salmonids. This leads to reduced absorptive capacity, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 110 publications
1
22
1
1
Order By: Relevance
“…In particular, cytokines are immune-modulating agents acting as pro-inflammatory mediators ( il1b and tnfa ) or playing an important role in the adaptive immunity response, as in the case of il10 [ 77 ]. The upregulation of cytokines and other molecular mediators has been observed as a common response to low FM-based diets in several fish species [ 78 ]. In this regard, Estruch et al [ 69 ] demonstrated that a long-term feeding period (22 weeks) with a Vp-based diet led to changes in the inflammatory and immune-related gene expression at the intestinal level in gilthead seabream.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cytokines are immune-modulating agents acting as pro-inflammatory mediators ( il1b and tnfa ) or playing an important role in the adaptive immunity response, as in the case of il10 [ 77 ]. The upregulation of cytokines and other molecular mediators has been observed as a common response to low FM-based diets in several fish species [ 78 ]. In this regard, Estruch et al [ 69 ] demonstrated that a long-term feeding period (22 weeks) with a Vp-based diet led to changes in the inflammatory and immune-related gene expression at the intestinal level in gilthead seabream.…”
Section: Discussionmentioning
confidence: 99%
“…In carnivorous fish species, almost 20–40% of fishmeal protein can be replaced with SBM protein without adversely affecting gut health 41 . However, high SBM protein proportions may threaten fish immunity and intestinal mucosa function, particularly in carnivorous species 42 …”
Section: Microbiome Composition Of Teleost Mucosamentioning
confidence: 99%
“…41 However, high SBM protein proportions may threaten fish immunity and intestinal mucosa function, particularly in carnivorous species. 42 The oropharynx is among the sections of the digestive tract with the highest microbial densities and has been studied extensively in mammals. 66 However, far fewer studies have focused on the microbial diversity of the teleost oropharynx.…”
Section: Ta B L Ementioning
confidence: 99%
“…With its high protein content, attractive cost and availability, SBM is one of the most widely used plant-based ingredients to reduce reliance on marine-derived aqua feed ingredients. Dietary inclusion of SBM is widely known to cause effects on gut health and associated microbiota due its content of antinutritional factors, such as saponins, which can cause pathological effects on gut morphology and inflammation, particularly in carnivorous fish (reviewed in [ 129 , 130 ]). Fishmeal replacement by SBM in aqua feeds is typically between 20 and 40%, at which enteritis can be detected in both omnivorous and carnivorous marine and freshwater fish [ 129 ].…”
Section: Dietary Oxidative Distress Challenges Models In Poultry Swine and Fishmentioning
confidence: 99%